A top-down multiregional econometric model of the Philippines - Danao, Rolando A. (1992)
This paper presents the results of the estimation and historical simulation of a system of top-down regional econometric models for the regions of the Philippines. The structure of the model ensures that the regional forecasts will be consistent with national forecasts. The dynamic historical simulations show that the predicted values of the national variables track their actual values quite well.
Includes bibliographical references (page 61).
Keywords: Econometric models